METHODOLOGICAL PRINCIPLES OF ASSESSMENT AND THE INSTITUTIONAL ROLE OF AUTHORITIES MANAGING THE FOREIGN STATE DEBT OF UKRAINE - RAZINKOVA Mіla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The methodical principles of assessment have been improved and the institutional role of the external public debt management bodies of Ukraine has been identified in conditions of geopolitical instability. It remains important to achieve a reduction in the size of the debt burden; reformatting the structure of the state debt in favor of its internal component, as well as establishing uniform debt repayment schedules with a possible extension of their terms and an increase in the average term of their fulfillment; continuation and deepening of cooperation with international financial organizations and governments of foreign countries regarding preferential financing of the country’s reconstruction and modernization in the post–war period of development, primarily on the basis of the implementation of innovative and investment development of the national economy. The results of the analysis of the retrospective and current state of application of the mechanism for managing state borrowing and guarantees of Ukraine, first of all, point to the undisputed conclusion about the ambiguity of the role of external state debt in stimulating economic growth, stabilizing state finances, and achieving price and financial stability. The assessment of the effectiveness of the relevant institutional authorities in the management of Ukraine’s external public debt was carried out using generally recognized indicators of debt security in world practice. The values of absolute and relative indicators of determining the state of management of state external debt obligations, during the selected time period of the study, were almost constantly influenced by both external and internal transformational or geopolitical factors (changes in the political system in the country, annexation of parts of the eastern and southern territories, a change in the geopolitical course of Ukraine’s development, the COVID–19 pandemic and the most significant problem – the war).